PENINGKATAN STABILITAS TEGANGAN STATIS DENGAN PENEMPATAN OPTIMAL STATCOM PADA SISTEM KELISTRIKAN BALI 16-BUS - Ni Putu Agustini; I Made Wartana (MULTITEK INDONESIA, 2020)
Voltage instability is mainly related to reactive power imbalances. The durability of the bus in the power system depends on the reactive power support that the bus can receive from the system. Since the system approaches the maximum loading point (MLP) or the voltage breakdown point, the real and reactive power loss increases rapidly. Therefore, the reactive carrying capacity must be local and adequate. This research studies the effect of using one type of Flexible AC Transmission System (FACTS), Static Synchronous Compensator (STATCOM), on increasing the Static Voltage Stability margin. STATCOM AC and DC representations used in the Continuation Power Flow (CPF) process in static voltage stability studies. The effectiveness of the proposed method has been practically simulated on the Bali 16-bus electrical system to investigate the system loading capacity increase. From simulations carried out with installing the modern controller in the best location, an increase in the endurance margin of the power system can obtain significantly.